Torsion of hydrogel cylinder with a chemo-mechanical coupled nonlinear elastic theory. (1st July 2022) - Zheng, Chengxiang; Wu, Tao; Deng, Zichen
Abstract: In this paper, a chemo-mechanically coupled elastic model is proposed for hydrogel based on the classical physical constitutive theory. This model includes a hydrostatic pressure dependent constant, two linear Lamé constants and three second-order elastic constants, where all the constants are coupled with the chemical field. The influences of key chemical and physical parameters are investigated on the elastic constants, and the deformation of a cylinder are then analytically studied subject to torsion in solvent through linear and nonlinear approaches. Both methods may reproduce the conventional relation between the torque and twist angle of classical mechanics, which incorporate the effect of the chemically coupled shear modulus. The results reveal that a negative Poynting effect is demonstrated that the cylinder tends to shorten on twisting, and that the chemical potential has significant effect on the elastic constants and subsequently on the deformation and mechanical behavior of hydrogels. Further studies show that the Flory parameter and the degree of crosslinking also have important impact on the torsion of hydrogels.